Lipid peroxidation and electrogenic ion transport in the jejunum of the vitamin E deficient rat. - Lindley, K J (1994)
Increased concentrations of reactive oxygen species in children with depleted antioxidant defences have been implicated in a cycle of malnutrition, malabsorption, and infection leading to protracted diarrhoea. A rat model of chronic vitamin E deficiency has been used to study the effects of antioxidant depletion on jejunal structure and function in vitro. Basal intestinal short circuit current (Isc), a measure of net electrogenic ion movement across the intestinal epithelium, was greater in chronically vitamin E deficient jejuna than controls, as was the electrogenic secretory response to aminophylline and Escherichia coli STa but not to bethanechol. The galactose stimulated current was also greater in vitamin E deficient jejuna. Indices of lipid peroxidation (concentrations of thiobarbituric acid reactive substances and malondialdehyde) were increased in the vitamin E deficient small bowel. Small intestinal brush border membranes from vitamin E deficient animals displayed changes in both static and dynamic components of membrane fluidity measured by steady state fluorescence polarography. The results of these studies support the hypothesis that oxidative stress in subjects with compromised antioxidant defences results in small intestinal hypersecretion, which could predispose to or perpetuate protracted diarrhoea.